PROMOTING LAND REGISTRATION EQUITY THROUGH SUBSIDIES AND LOW-COST FINANCING MECHANISMS - Jojo Juhaeni (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the effectiveness of government subsidies and low-cost financing mechanisms in improving equal access to land registration, especially for low-income groups and rural communities. Using a descriptive qualitative approach, data was obtained through in-depth interviews, observations, and documentation of subsidy recipient communities, land officials, and local governments. The results of the study show that the subsidy for land registration fees significantly reduces the financial barriers that have been the main barrier for the poor in obtaining land certification. Meanwhile, low-cost financing mechanisms such as incremental payments and microcredit have been proven to help households manage the cost burden without interfering with other economic needs. Nevertheless, the effectiveness of these two instruments is strongly influenced by local institutional conditions, including bureaucratic complexity, administrative capacity, and level of transparency of land services. Geographical and social inequalities were also found, where remote areas and vulnerable groups benefited less than areas with stronger institutions. These findings confirm that cost interventions need to be accompanied by institutional improvements and increased community land literacy so that subsidies and cheap financing can function optimally as an instrument for equitable access to land registration.